2017
DOI: 10.1016/j.cgh.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Nausea in Children With Functional Abdominal Pain Predicts Poor Health Outcomes in Young Adulthood

Abstract: Background & Aims Nausea is common among children with functional abdominal pain (FAP). We evaluated the relation of nausea to short- and long-term morbidity in pediatric patients with FAP. Methods We performed a prospective study of 871 children with FAP (8–17 years old) seen in a pediatric gastroenterology practice; follow-up data were collected from 396 of the patients 8.7±3.3 years later. Participants were defined as having significant nausea if they reported nausea “a lot” or “a whole lot” within the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 33 publications
5
41
0
Order By: Relevance
“…Studies have shown that nausea is a common symptom in children with functional abdominal pain disorders [18] and that some children have nausea or vomiting that presents in a non-stereotypical and cyclical fashion [19]. Moreover, studies have shown that nausea is a highly invalidating symptom and that children with severe and prolonged nausea have a poor quality of life [20]. As a result, the Rome IV criteria established two new diagnoses: functional nausea and functional vomiting.…”
Section: Functional Disorders Of Nausea and Vomitingmentioning
confidence: 99%
“…Studies have shown that nausea is a common symptom in children with functional abdominal pain disorders [18] and that some children have nausea or vomiting that presents in a non-stereotypical and cyclical fashion [19]. Moreover, studies have shown that nausea is a highly invalidating symptom and that children with severe and prolonged nausea have a poor quality of life [20]. As a result, the Rome IV criteria established two new diagnoses: functional nausea and functional vomiting.…”
Section: Functional Disorders Of Nausea and Vomitingmentioning
confidence: 99%
“…Nausea is a common and debilitating symptom that is increasingly recognized among children with FAPDs, but yet poorly described . A community survey identified nausea in as many as 15.9% of school‐aged children .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the presence of nausea in that study correlated with poor school and social functioning and uniquely predicted social disability. Further, a long‐term study in children with FAPDs demonstrated that those with co‐existent nausea compared to those without nausea suffered from more somatic, GI, and psychiatric symptoms that continued into young adulthood …”
Section: Introductionmentioning
confidence: 99%
“…Although that interpretation is no longer widely held, the idea that somatization has psychological underpinnings has persisted and suggestions have been made that somatization may be due to increased psychological distress or a learned behavior to attend to physical symptoms . Some studies show that comorbidities such as nausea, incontinence, and fibromyalgia increase the risk of anxiety and depression for children with FAPD . In addition, evidence that attention to pain stimuli can be a learned behavior has come from studies showing that FAPD patients have an (subconscious) attentional bias toward pain .…”
Section: Fapd and Somatizationmentioning
confidence: 99%
“…Some studies show that comorbidities such as nausea, incontinence, and fibromyalgia increase the risk of anxiety and depression for children with FAPD. 15,36,45 In addition, evidence that attention to pain stimuli can be a learned behavior has come from studies showing that FAPD patients have an (subconscious) attentional bias toward pain. 46,47 However, it has also been suggested that somatization may be due to autonomic nervous system dysregulation, decreased sensation thresholds for bodily symptoms, increased subclinical inflammation, or deficits in cellular metabolism.…”
Section: Key Pointsmentioning
confidence: 99%